2009
DOI: 10.1111/j.1439-0426.2009.01364.x
|View full text |Cite
|
Sign up to set email alerts
|

Kootenai River velocities, depth, and white sturgeon spawning site selection – a mystery unraveled?

Abstract: The Kootenai River white sturgeon Acipenser transmontanus population in Idaho, US and British Columbia (BC), Canada became recruitment limited shortly after Libby Dam became fully operational on the Kootenai River, Montana, USA in 1974. In the USA the species was listed under the Endangered Species Act in September of 1994. Kootenai River white sturgeon spawn within an 18-km reach in Idaho, river kilometer (rkm) 228.0-246.0. Each autumn and spring Kootenai River white sturgeon follow a Ôshort two-stepÕ migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…323 Due to lack of a positive recruitment effect a score of -2 was assigned for both contaminant 324 hypotheses. 586 The present findings add to a growing list of studies highlighting the importance of 587 substrate conditions in sturgeon spawning habitat (see Paragamian et al 2009;Kerr et al 588 2010; Du et al 2011). Most hypotheses received scores of -2 based on their 330 inability to explain the delayed recruitment failure of the Waneta group.…”
mentioning
confidence: 65%
“…323 Due to lack of a positive recruitment effect a score of -2 was assigned for both contaminant 324 hypotheses. 586 The present findings add to a growing list of studies highlighting the importance of 587 substrate conditions in sturgeon spawning habitat (see Paragamian et al 2009;Kerr et al 588 2010; Du et al 2011). Most hypotheses received scores of -2 based on their 330 inability to explain the delayed recruitment failure of the Waneta group.…”
mentioning
confidence: 65%
“…A more sophisticated approach was necessary (Paragamian et al 2009, McDonald et al 2010). Fisheries and hydrology researchers collaborated to determine whether the spawning habitat had been changed by Libby Dam operations.…”
Section: Analytical Fusion Of Spawning Location and Fluvial Processesmentioning
confidence: 99%
“…Modeling suggested that higher discharges approximating 1600 m 3 s −1 or more for a period of 2 wk would likely provide more suitable spawning and rearing conditions (Paragamian et al 2009, McDonald et al 2010.…”
Section: Analytical Fusion Of Spawning Location and Fluvial Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no clear understanding of the cause of recruitment failure; however, there is consensus that river regulation is a significant contributing factor (McAdam et al 2005;Paragamian et al 2001Paragamian et al ,2009). …”
Section: Whole-body Glycogen Concentration Versus (A) Days Post Hatmentioning
confidence: 99%